OPTIMALISASI HASIL TANGKAPAN MELALUI PELATIHAN PENGGUNAAN FISH FINDER PADA KELOMPOK NELAYAN PULAU SAUGI - Hasriyanti; Hildayanti (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2026)
The use of science and technology in resource-based capture fisheries is a crucial effort to support the sustainability of fishing businesses. One technology that can be utilized in fishing activities is the fish finder, a device used to detect the presence of fish in the water. This community service activity aims to improve the knowledge and skills of the Saugi Island fishing community in using fish finders, thereby helping them locate fish and increase their catch. The method used was a community development approach through training that combined theory, field practice, and focus group discussions. The training went well and received a positive response from participants, who demonstrated high enthusiasm throughout. The training program was conducted in two phases: a theory class and a practical class. In the theory session, participants gained an understanding of the development and use of fish finders in fisheries, while in the practical session, participants operated the equipment directly on their boats. Based on monitoring and evaluation results, the use of fish finders provides various benefits for fishermen, including facilitating fish detection, reducing fishing operational costs, increasing catches, and helping to more effectively determine fishing grounds.